Encounters at the Religious Edge: Variation in Religious Expression Across Interfaith Advocacy and Social Movement Settings. Issue 4 (December 2014) - Yukich, Grace; Braunstein, Ruth
<x xml:space="preserve">Abstract</x> In a time of increasing religious diversity, interfaith political coalitions have become important settings for interreligious interaction, but little research has explored the types of religious expression that are generated therein. Prevailing theories in the sociology of religion indicate that interaction with religious others results in dilution of traditional religious commitments or production of stronger boundaries. But emerging perspectives in cultural sociology shift attention from individual religious commitments to the ways in which settings shape different styles of religious expression. Insights about edge spaces drawn from urban theory suggest that religiously diverse settings can be generative of new types of religious practices. We apply these insights to the study of interfaith activism by drawing on interviews and ethnographic fieldwork with religious advocacy professionals and activists working in interfaith coalitions. Conceptualizing the sites of these interfaith encounters as edge spaces, we analyze variation in the types of religious expression that occur in interfaith settings. We find that both aggregative and integrative practices are produced, but these vary depending on the goals and structure of the setting, as well as participants' accountability to outside religious gatekeepers.